Unravelling the Mysteries Factors Influencing Perceptions of Early Marriage - Nurlia Catur Utami; Herlina Yusuf; Nurjanah (Yayasan Sinergi Kawula Muda, 2021)
The preliminary research was conducted at Office of Religious Affairs of Mantikulore District. The data for 2020 shows that the number of Early Marriages in the Office of Religious Affairs of Mantukulore District is 7 people, and there i an increase in 2021 as many as 14 people which shows that there is a very rapid increase from 2020-2021 related to early marriage. The purpose of this research is to determine the factors of the students' perception on early marriage. This is an analytical survey method using a cross sectional approach. The sample was taken by random sampling technique. The number of samples is 63 people and used Chi-square test data analysis. The results of the research indicate that there is a correlation between students' knowledge and perceptions of early marriage as evidenced by statistical tests with p value = 0.031 < 0.05, there is a socio-economic correlation with perceptions with p-value = 0.001 < 0.05 and there is a correlation between parental attitudes and with p value = 0.021 > 0.05. The researcher suggests to always provide information related to the impact of early marriage to students through socialization or counselling so that students better understand the impacts of early marriage to reduce the occurrence of early Marriage.